Associations of plasma renin with 10-year cardiovascular mortality, sudden cardiac death, and death due to heart failure - Tomaschitz, Andreas; Pilz, Stefan; Ritz, Eberhard; Morganti, Alberto; Grammer, Tanja B.; Amrein, Karin; Boehm, Bernhard O.; März, Winfried (European heart journal, 2011)
Renin is the key regulator of the renin-angiotensin-aldosterone system. Previous studies have reported conflicting results on the relation of plasma renin with fatal cardiovascular events. This study in a large cohort of patients sought to evaluate the association between plasma renin concentration (PRC) and cardiovascular mortality after long-term follow-up of almost 10 years.Plasma renin concentration [median: 11.4 (6.0-24.6) pg/mL] was measured in 3303 patients (mean age: 62.7 ± 10.6 years; 30.3% women) referred to coronary angiography. After a median follow-up of 9.9 years, 554 participants (16.8%) with PRC measurement at baseline had died due to fatal cardiovascular events. Multivariable-adjusted Cox analysis revealed that when compared with participants in the lowest PRC quartile, those in the highest quartile were at increased risk of cardiovascular mortality (hazard ratio: 1.79, 95% CI 1.28-2.48). Analyses of specific causes of cardiovascular death showed that for each standard deviation increase in log-PRC there was a 22% (P = 0.006) increase in risk of sudden cardiac death and a 23% (P = 0.033) greater risk of death due to heart failure. The association of PRC with cardiovascular mortality remained stable after adjustment for established cardiovascular risk factors, ongoing antihypertensive medication, immunoreactive angiotensin II, and aldosterone levels. Age, N-terminal pro-B-type natriuretic peptide levels, coronary artery disease, the use of angiotensin-converting enzyme-inhibitors, beta-blockers, diuretics, and kidney function were important effect modifiers.Plasma renin concentration is associated with long-term cardiovascular mortality in patients referred to coronary angiography. Further intervention studies should determine whether renin is a potential therapeutic target or only a marker of mortality risk in various cardiovascular risk groups.
Gesehen am 10.11.2022